The Green Mill murder - Greenwood, Kerry (Greenwood, Kerry. Phryne Fisher mystery, 2017)
Phryne Fisher is doing one of her favorite things --dancing at the Green Mill (Melbourne's premier dance hall) to the music of Tintagel Stone's Jazzmakers, the band who taught St Vitus how to dance. And she's wearing a sparkling lobelia-coloured georgette dress. Nothing can flap the unflappable Phryne--especially on a dance floor with so many delectable partners. Nothing except death, that is. The dance competition is trailing into its last hours when suddenly, in the middle of "Bye Bye Blackbird" a figure slumps to the ground. No shot was heard. Phryne, conscious of how narrowly the missile missed her own bare shoulder, back, and dress, investigates. This leads her into the dark smoky jazz clubs of Fitzroy, into the arms of eloquent strangers, and finally into the the sky, as she follows a complicated family tragedy of the great War and the damaged men who came back from ANZAC cove. Phryne flies her Gypsy Moth Rigel into the Australian Alps, where she meets a hermit with a dog called Lucky and a wombat living under his bunk....and risks her life on the love between brothers.